2016
DOI: 10.1080/15412555.2016.1240159
|View full text |Cite
|
Sign up to set email alerts
|

Can Assessment of Disease Burden Prior to Changes in Initial COPD Maintenance Treatment Provide Insight into Remaining Unmet Needs? A Retrospective Database Study in UK Primary Care

Abstract: This retrospective cohort study aimed to assess treatment patterns over 24 months amongst patients with chronic obstructive pulmonary disease (COPD), initiating a new COPD maintenance treatment, and to understand clinical indicators of treatment change. Patients included in the study initiated a long-acting β-agonist (LABA), a long-acting muscarinic antagonist (LAMA), or a combination of LABA and an inhaled corticosteroid (ICS/LABA) between January 1, 2009, and November 30, 2013, as recorded in the United King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…This finding suggests that the assessment of dyspnea, a cardinal symptom of COPD, may not be well integrated into daily practice, perhaps owing to the difficulty for GPs to clinically appreciate this primary indicator. Other observational studies identified comorbid asthma, high exacerbation rates, airflow obstruction, and comorbidities as determinants of initial maintenance therapy,40 whereas a retrospective database study in UK primary care reported only a minor role of exacerbations in treatment modifications (switching or augmenting maintenance therapy) 24. In addition, ~50% of patients who started an initial maintenance treatment with LABD therapy in our study did so in combination with ICS.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This finding suggests that the assessment of dyspnea, a cardinal symptom of COPD, may not be well integrated into daily practice, perhaps owing to the difficulty for GPs to clinically appreciate this primary indicator. Other observational studies identified comorbid asthma, high exacerbation rates, airflow obstruction, and comorbidities as determinants of initial maintenance therapy,40 whereas a retrospective database study in UK primary care reported only a minor role of exacerbations in treatment modifications (switching or augmenting maintenance therapy) 24. In addition, ~50% of patients who started an initial maintenance treatment with LABD therapy in our study did so in combination with ICS.…”
Section: Discussioncontrasting
confidence: 49%
“…With multiple classes of drugs now available for the pharmacological treatment of COPD in France, the treatment armamentarium available to clinicians has expanded; however, these options have reintroduced instability and uncertainty regarding treatment pathways in COPD. For example, a recently published retrospective cohort study set within UK primary care showed differential patterns of escalation and switch, with multiple pathways for escalating to triple therapy 24…”
Section: Introductionmentioning
confidence: 99%
“…For example, a subset of patients with COPD demonstrate increased eosinophilic airway inflammation during exacerbations 19. Furthermore, peripheral blood eosinophil counts of ≥150 cells/µL have been shown to be associated with an increased risk of AECOPDs 1921. Importantly, patients with increased blood eosinophil counts have a greater probability of benefit from treatment with ICS13,2224 and treatments that specifically target eosinophilic inflammation 25…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a recent study showed that COPD exacerbations were the most significant factor for escalation 17. In another study,18 results showed that exacerbations had only a minor influence on treatment augmentation and that it was driven more by the need for rescue medication and assessment of dyspnea. In our study of patients with COPD experiencing an exacerbation event, it can be considered that exacerbations were the driver of MITT initiation and, in these cases, initiation sooner after the exacerbation had beneficial effects versus later MITT initiation.…”
Section: Discussionmentioning
confidence: 99%